Characterization of drop aerodynamic fragmentation in the bag and sheet-thinning regimes by crossed-beam, two-view, digital in-line holography. (September 2017) - Guildenbecher, Daniel R.; Gao, Jian; Chen, Jun; Sojka, Paul E.
Highlights: An improved digital in-line holography diagnostic is proposed which utilizes two stereo views. Measured out-of-plane particle position uncertainty is shown to be improved by an order of magnitude compared to traditional single-view digital in-line holography. Tens of thousands of fragments are quantified at a given condition which is many orders-of-magnitude improvement compared to previous efforts. The volumetric size distribution of fragments produced by the aerodynamic breakup of a drop is found to be multi-model in the bag regime and mono-modal in the sheet-thinning regime. At high Weber number the fragment size distribution follows the Simmons universal root-normal distribution. Abstract: When a spherical liquid drop is subjected to a step change in relative gas velocity, aerodynamic forces lead to drop deformation and possible breakup into a number of secondary fragments. To investigate this flow, a digital in-line holography (DIH) diagnostic is proposed which enables rapid quantification of spatial statistics with limited experimental repetition. To overcome the high uncertainty in the depth direction experienced in previous applications of DIH, a crossed-beam, two-view configuration is introduced. With appropriate calibration, this diagnostic is shown to provide accurate quantification of fragment sizes, three-dimensional positions and three-component velocities in a large measurement volume. These capabilities are applied to investigate the aerodynamic breakup of drops at two non-dimensional Weber numbers, We, corresponding to the bag ( We = 14) and sheet-thinning ( We = 55) regimes. Ensemble average results show the evolution of fragment size and velocity statistics during the course of breakup. Results indicate that mean fragment sizes increase throughout the course of breakup. For the bag breakup case, the evolution of a multi-mode fragment size probability density is observed. This is attributed to separate fragmentation mechanisms for the bag and rim structures. In contrast, for the sheet-thinning case, the fragment size probability density shows only one distinct peak indicating a single fragmentation mechanism. Compared to previous related investigations of this flow, many orders of magnitude more fragments are measured per condition, resulting in a significant improvement in data fidelity. For this reason, this experimental dataset is likely to provide new opportunities for detailed validation of analytic and computational models of this flow.